Effects of a Comprehensive, Intensive Lifestyle Intervention Combined with Metformin Extended Release in Obese Adolescents. (10th November 2014) - Clarson, Cheril L.; Brown, Hilary K.; De Jesus, Stefanie; Jackman, Michelle; Mahmud, Farid H.; Prapavessis, Harry; Robinson, Tracy; Shoemaker, J. Kevin; Watson, Margaret; Dowd, A. Justine; Hill, David J.
Abstract : Objective . To assess a comprehensive, intensive lifestyle intervention in combination with metformin extended release (MXR) or placebo on body mass index (BMI) and risk factors for type 2 diabetes and cardiovascular disease in obese adolescents. Study Design . Sixty-nineobese adolescents (mean BMI 32.5) received a comprehensive lifestyle intervention with structured dietary, physical activity, and behavioral components for 24 months. Subjects were randomized to 1 of 4 groups: MXR (33) 2, 000 mg daily or placebo, with either moderate or vigorous intensity exercise for the first 3 months. Subsequently the exercise intervention was the same for all 4 groups. Results. Anthropometry measurements did not differ with initial exercise intensity at any time. At 3 months % body fat decreased in all 4 groups (P < 0.006 ). BMI and % body fat decreased in the MXR groups, but not the placebo groups, at 6 (−0.88, −3.16) and 12 months (−0.56, −2.34) (P < 0.05 ). Insulin resistance, fasting blood glucose, and leptin improved in all groups at 6 and 12 months. A high subject attrition rate (58%) occurred by 24 months. Conclusion . A comprehensive, intensive lifestyle intervention combined with MXR led to a decline in BMI and % body fat at 1 year independent of initial exercise intensity. This trial is registered with ClinicalTrials.gov NCT00934570 .